PERAN KEPEMIMPINAN DALAM IMPLEMENTASI STRATEGI KONTEN MEDIA SOSIAL UNTUK MENINGKATKAN BRAND AWARENESS UMKM TOKO KUE MPOK RUKIAH - Siti Nurul Aini; Aldina Shiratina (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the role of leadership in the implementation of social media content strategy to enhance brand awareness of MSME Toko Kue Mpok Rukiah, which previously had no digital presence. The primary issue faced by the business was limited market reach due to the suboptimal use of social media. This study employed an implementative approach using the SOSTAC model (Situation, Objectives, Strategy, Tactics, Action, Control) through the management of Instagram and TikTok platforms. In practice, the leader played a key role in formulating content strategies, coordinating content production, and monitoring performance based on Key Performance Indicators (KPIs). The content strategy was categorized into four types: promotional, informational, educational, and entertainment. The findings indicate that each content type contributed differently to social media performance. Entertainment content generated the highest reach, while informational content achieved the highest engagement rate of 3.87%, indicating that information-based content is more effective in driving audience interaction than direct promotional content. Overall, the leader’s role in directing a structured and consistent content strategy contributed to increased visibility and audience engagement, thereby enhancing the brand awareness of the MSME.